Frequency of Cerebrospinal Fluid Leakage in Patients with Caries Spine Treated with Cage Fixation Procedure with Anterior Approach (Medical Forum Monthly, 2024)
ABSTRACTObjective: To determine the frequency of cerebrospinal fluid leakage in patients with caries spine treated with cage fixation procedure with anterior approach.Study Design: Descriptive studyPlace and Duration of Study: This study was conducted at the Department of Neurosurgery Bahawal Victoria Hospital, Bahawalpur from November 2014 to May 2015.Materials and Methods: A total of 157 patients with proven tuberculosis and having significant kyphosis (>40° of segmental kyphosis) and instability (anteroposterior translation; >40° of segmental kyphosis), 30 to 60 years of age were included. Patients with h/o previous operation and those who were not willing to participate excluded from the study. All patients were followed for 1 month for presence or absence of CSF leakage (yes/no) and final outcome was noted.Results: There were 102 (64.97%) males while 35.03% patients were females with mean age of 48.07±8.35 years (30-60 years). Cerebrospinal fluid leakage was found in 13 (8.28%) patients, whereas no CSF leakage in 144 (91.72%) patients.Conclusion: The cage fixation procedure with anterior approach is safe and effective with low rate of cerebrospinal fluid leakage.